Association of follicle-to-oocyte index and clinical pregnancy in IVF treatment: A retrospective study of 4,323 fresh embryo transfer cycles - Li, Peiyi; Chen, Zhiyun (Frontiers in Endocrinology, 2022)
Objective: To investigate whether the follicle-to-oocyte index (FOI: (number of retrieved oocytes/ antral follicle count) × 100) was associated with clinical pregnancy after fresh cleavage transfer. Design: Retrospective cohort analysis. Setting: A single IVF center in a public hospital. Patients: In total, 4,323 fresh embryo transfer cycles from August 1st, 2011 to January 31st, 2022 were retrospectively analyzed. Data were designated into three groups according to FOI tertile values. Interventions: None. Main Outcome Measure: Clinical pregnancy rate (CPR). Results: 4,323 patients were included in the study. Patients were divided according to their FOI into low (FOI ≤0.70, n =1434), medium (FOI = 0.71-0.95, n = 1070), and high (FOI= 0.96-1.00, n = 1819) tertile groups. A significant statistical increase in CPR from the lowest to the highest tertile FOI group was detected (47.28%, 51.78% and 51.57%; P =0.026). After adjusted for potential confounders, multivariate logistic regression analysis revealed a positive association between FOI and CPR (OR=1.57; 95 CI%: 1.18-2.11). Each standard deviation increments in FOI (SD=0.24) corresponded to a 20% increase in CPR. Trend analysis also showed that FOI tertile groups were positively associated with CPR (P for trend =0.010). Smooth curve fitting indicated the existence of a linear relationship across the entire range of FOI. No optimal cutoff value of FOI for prognosing CPR was found in smooth curve fitting analysis. Moreover, subgroup analyses suggested that the association was significantly stronger in single cleavage transfer cycle (OR=2.04; 95% CI: 1.14-3.65). Conclusions: FOI is an independent variable in prediction for CPR in fresh embryo transfer cycle, especially in single cleavage transfer cycle.